NOTES ON THE RECORD OF GOBLIN SHARK (Mitsukurina owstoni Jordan, 1898) FROM INDONESIA - Fahmi, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2017)
A goblin shark, Mitsukurina owstoni,was captured by deepwater shark longline targeting squaloid sharks off Palabuhanratu, West Java, Indonesia at about 200 m depth. Morphological measurements were taken and compared to other records from Australia, New Zealand and Japan. This new recordfrom Indonesian waters extends the distribution of this species in the Indian Ocean.